Oil Wealth and Real Exchange Rates: The FEER for Norway - Q. Farooq Akram (Norges Bank, 2004)
It is often argued that Norway's sizeable net foreign assets based on its petroleum wealth imply an appreciation of its real exchange rate to a permanently strong level. We investigate this issue within the framework of the fundamental equilibrium real exchange rate (FEER) approach. It is shown that the strength of the FEER depends on the share of imports that can be financed by petroleum (based) revenues. Projections of the FEER over a long horizon suggest that the petroleum wealth implies a stronger equilibrium exchange rate than the rate that would have balanced (non-petroleum) foreign trade in each period. However, the FEER depreciates steadily over time with growth in imports relative to petroleum revenues and converges towards the rate that balances foreign trade. A permanently strong FEER presupposes that e.g. imports stay constant over time. Our results are in accord with the behaviour of the real exchange before and after the discovery of Norway's petroleum resources.
hdl:11250/2498539
Keywords: C32; C53; F31; F41; 330; FEER; equilibrium real exchange rate; econometric analysis